2019
DOI: 10.1111/pedi.12848
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics, and diabetes management in children with comorbid autism spectrum disorder and type 1 diabetes

Abstract: Objective: To determine autism spectrum disorder (ASD) prevalence within our pediatric type 1 diabetes (T1D) clinic population and determine clinical characteristics and technology used by individuals with both ASD and T1D compared to matched controls with T1D alone and compared to our overall pediatric T1D clinic.Methods: Medical chart review showed 30 individuals with both ASD and type 1 diabetes (ASD + T1D). Controls (n = 90) were matched for age, sex, race/ethnicity, and T1D duration. ASD + T1D was compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…These findings complement the work of Stanek et al [ 9 ] and Bethin et al [ 10 ], who found that CGM use was the same among children with T1D and ASD as it was among those with T1D but without ASD, whereas insulin pump use was lower for those with both T1D and ASD. This qualitative work adds some explanatory context, as caregivers identified that sensory issues can preclude the successful use of insulin pumps and that successful solutions for some have included the use of tubeless pumps and desensitization techniques, such as the routine use of band-aids before attempting to use diabetes technology.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings complement the work of Stanek et al [ 9 ] and Bethin et al [ 10 ], who found that CGM use was the same among children with T1D and ASD as it was among those with T1D but without ASD, whereas insulin pump use was lower for those with both T1D and ASD. This qualitative work adds some explanatory context, as caregivers identified that sensory issues can preclude the successful use of insulin pumps and that successful solutions for some have included the use of tubeless pumps and desensitization techniques, such as the routine use of band-aids before attempting to use diabetes technology.…”
Section: Discussionsupporting
confidence: 89%
“…It is not surprising that this study did not achieve statistical significance, as it was not powered to do so and the sample size was chosen for the greater qualitative focus here. This also echoes comments by Bethin et al [ 10 ] and Stanek et al [ 9 ] that further work is needed to be able to better support these children and their families. From this study specifically, we propose that further research with larger sample sizes is needed to continue to explore the potential relationships between the degree of functioning related to ASD and glycemic control.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The prevalence of ASD among children with T1DM who attended a diabetic clinic in Toronto was greater than the general population (Freeman et al, 2005). In line with this study, it has been clarified that the prevalence of ASD in T1DM patients in Colorado and Ontario were 1.16% and 0.9%, respectively, both higher than the ASD prevalence in the normal population living in Colorado (0.7%) (Stanek et al, 2019). The same authors found a lower HbA1c level (P<0.0001) and insulin pump (P<0.0001) in ASD+T1DM patients compared to T1DM patients.…”
Section: Known Concomitant Autoimmune Diseases In Patients With Asdsupporting
confidence: 73%
“…Up to 1 in 59 children in the United States have been identified with ASD [7], and the reported prevalence of ASD is also increasing [3,7]. There is little research regarding the prevalence of individuals with both ASD and T1D in the United States [3,[6][7][8], although a recent study found the prevalence of ASD in the pediatric T1D population in 1 clinic to be 1.16% (95% CI 0.96-1.26) [9]. An additional study reported that among 10,032 participants from the T1D Exchange Clinic Network, 159 (1.58%) had T1D and ASD [10].…”
Section: Introductionmentioning
confidence: 99%